Exploring the path of persisting dysfunctional expectations—Development of the immunization scale IMS - Ewen, Anne-Catherine I.; Rief, Winfried; Wilhelm, Marcel (Frontiers in Psychology, 2022)
Objectives Persistent dysfunctional expectations seem to be core features of mental disorders. The aim of this study was to develop a questionnaire that assesses mechanisms responsible for the consistency of dysfunctional expectations. Processes before (i.e., assimilation) and after (i.e., immunization) expectation-violating experiences have been considered. Design The Immunization Scale (IMS) is constructed and validated with the help of an explorative (EFA) and confirmatory factor analysis (CFA) in two conducted studies. Materials and methods For the first study, the initially formulated 75-item version was completed online by 230 (range 18–69) participants from a convenience sample. For the second study, 299 (range 18–62) participants completed the reduced scale at the first measurement point, 75 participants thereof also 1 month later. For validity and reliability analyses, participants in both studies provided demographic information, the Beck Depression Inventory (BDI-II), the Depressive Expectation Scale (DES), the Beck Anxiety Inventory (BAI), and the German version of the Acceptance and Action Questionnaire (FAH-II). Results The initial 75 items were reduced to 23 items. The EFA revealed three main factors, namely, negative expectations, assimilation, and cognitive immunization. The three-factor structure could be confirmed in study 2 by the CFA. Reliability measures showed an excellent internal consistency for the entire IMS. A very good test–retest reliability was found. Significant correlations resulted between the IMS and DES, BDI-II, BAI, and FAH-II, the highest for DES and FAH-II. Conclusion Psychometric properties of the IMS are promising. Future studies should verify the reliability and validity measures in other population samples. The IMS can be very useful in expectation research, especially in the examination of expectation-focused therapy.